2007
DOI: 10.1002/bmc.736
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of CYP1A2, CYP2A6, NAT‐2 and xanthine oxidase activities in a Greek population sample by the RP‐HPLC monitoring of caffeine metabolic ratios

Abstract: A RP-HPLC method was developed for the assessment of caffeine and its metabolites in urine and was used for the evaluation of the CYP1A2, CYP2A6, xanthine oxidase (XO) and N-acetyl-transferase-2 (NAT-2) in vivo activities in 44 Greek volunteers (21 men, 23 women). Spot urine samples were analyzed 6 h after 200 mg caffeine consumption, following a 30 h methylxantine-free diet. The major urinary caffeine metabolites are 1-methyluric acid (1U), 5-acetylamino-6-formylamino-3-methyluracil (AFMU), 1-methylxanthine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
93
3
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 48 publications
7
93
3
19
Order By: Relevance
“…Previous studies, using nicotine and cotinine as probes, showed an inhibitory effect of cigarette smoking on CYP2A6 enzyme activity [5,6]. Sex differences have been observed as well [4,[7][8][9][10], but the findings were not always consistent [11,12]. Nevertheless, the major cause for the observed variability in enzyme activity seems to be genetic polymorphisms of the CYP2A6 gene [1].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies, using nicotine and cotinine as probes, showed an inhibitory effect of cigarette smoking on CYP2A6 enzyme activity [5,6]. Sex differences have been observed as well [4,[7][8][9][10], but the findings were not always consistent [11,12]. Nevertheless, the major cause for the observed variability in enzyme activity seems to be genetic polymorphisms of the CYP2A6 gene [1].…”
Section: Introductionmentioning
confidence: 99%
“…Xanthine oxidase (XO) is a multifunctional enzyme responsible for oxidation processes of a wide range of substrates, including a number of endogenous compounds and several clinically important drugs [11,[13][14][15][16][17]. Previous studies, using radiochemical assay [13] or caffeine test [11,14,18,19], showed that XO activity differs among individuals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations